Silica and Silicon Based Nanostructures - Ternon, Céline (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Silica and silicon-based nanostructures are now well-understood materials for which the technologies are mature. The most obvious applications, such as electronic devices, have been widely explored over the last two decades. The aim of this Special Issue is to bring together the state of the art in the field and to enable the emergence of new ideas and concepts for silicon and silica-based nanostructures.